TELAAH FILSAFAT PENDIDIKAN ISLAM DAN IMPLIKASINYA TERHADAP PENDIDIKAN SEUMUR HIDUP MENUJU MASYARAKAT MADANI - Iwan Israwan (STAI Sebelas April Sumedang, 2020)
Civil society in the education aspect is the preparation of human resources with knowledge and civilian behavior through education. It is because the concept of civil society is part of the national education goal. All people may agree that education is important for building human quality, indicated by improving intelligence, knowledge, and skills since education is a strategic sector for the quality of human life by developing in the degree of welfare, a decrease in poverty, and the formation of various options and opportunities to develop themselves towards civil society. The complex problem in lifelong education is faced. Various policies have been made by the Indonesian government. However, in terms of implementation, it is found many obstacles, particularly in the mentality of the people who are lack motivation, so the education cannot be optimized as an institution that has broad community support. Therefore, civil society is important to be reviewed. The research objective is to examine the philosophy of Islamic education as a critical analysis of a philosophical concept, the interpretation of Islamic education, and its implications for lifelong education. The research method used a philosophical approach by seeking a good lesson or wisdom as well as truth. Researchers examined critically that: